Factors contributing to disease risk in pig production in Hung Yen - Nguyen Thi Thu Huyen; Pham Van Hung; Ninh Xuan Trung (2016)
In practice, many types of diseases happen in pig production in Hung Yen such as diarrhea, pneumonia, fever, blue ear, head edema and pasteurellosis, in which, the most widely and frequently observed disease is diarrhea and it often happens for piglet. Diseases may lead to a result of dead pigs. Cost of mortality is a kind of economic loss and it is estimated about 3.3 mil. VND/household/year and this loss accounts for about 13.6 percent of total income from pig production. In order to mitigate disease risk and mortality cost, it is necessary to investigate factors contributing to disease risk. Results of this paper indicate that driven factors contributing to disease risk are production scale, pig density, quality of veterinary services, contacting possibility between different groups and age classes, hygiene issue of pig house and waste treatment and sources of purchased piglets. In relation to solutions mitigating pig disease risk, local authorities should pay more attention on improving quality of veterinary services and it is necessary to have a master plan for pig industry development in region. In addition, pig farmers themselves should improve farming practices related to pig isolation and cleaning pig houses and should produce own piglets.